2019
DOI: 10.1128/iai.00641-19
|View full text |Cite
|
Sign up to set email alerts
|

Particles from the Echinococcus granulosus Laminated Layer Inhibit CD40 Upregulation in Dendritic Cells by Interfering with Akt Activation

Abstract: The larval stage of the cestode Echinococcus granulosus causes cystic echinococcosis in humans and livestock. This larva is protected by the millimeter-thick, mucin-based laminated layer (LL), from which materials have to be shed to allow parasite growth. We previously reported that dendritic cells (DCs) respond to microscopic pieces of the mucin gel of the LL (pLL) with unconventional maturation phenotypes, in the absence or presence of Toll-like receptor (TLR) agonists, including lipopolysaccharide (LPS).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
35
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(42 citation statements)
references
References 88 publications
(159 reference statements)
6
35
0
1
Order By: Relevance
“…In mouse bone marrow-derived dendritic cells (BMDC), in particular, pLL induce the expression of CD86 and enhance lipopolysaccharide (LPS)-elicited CD86 and interleukin 10 (IL-10) expression while blunting the responses of CD40 and IL-12p70 (as well as its subunit IL-12/23p40) to LPS (35). These changes elicited by pLL require actin dynamics, phosphatidylinositol 3-kinase (PI3K) class I, and probably the kinase Syk, but not particle phagocytosis, and appear to be receptor independent (36). These features match a mechanism termed "membrane affinity-triggered signaling" (MATS), proposed by Yan Shi to explain DC and macrophage responses to solid, mostly crystalline materials (38).…”
mentioning
confidence: 99%
“…In mouse bone marrow-derived dendritic cells (BMDC), in particular, pLL induce the expression of CD86 and enhance lipopolysaccharide (LPS)-elicited CD86 and interleukin 10 (IL-10) expression while blunting the responses of CD40 and IL-12p70 (as well as its subunit IL-12/23p40) to LPS (35). These changes elicited by pLL require actin dynamics, phosphatidylinositol 3-kinase (PI3K) class I, and probably the kinase Syk, but not particle phagocytosis, and appear to be receptor independent (36). These features match a mechanism termed "membrane affinity-triggered signaling" (MATS), proposed by Yan Shi to explain DC and macrophage responses to solid, mostly crystalline materials (38).…”
mentioning
confidence: 99%
“…We have previously reported that exosome-like vesicles induce maturation of BMDCs with an increase of CD86 and a slight downregulation in the expression of MHC II molecule 56 . Likewise, previous reports have shown a weak maturation phenotype in mouse and human DCs upon stimulation with Eg antigens in combination with potent immunogens 36,38,57,[57][58][59][60][61] . Uptake and processing of antigens by immature DCs are critical steps in producing an immune response.…”
Section: Discussionmentioning
confidence: 56%
“…In line with these results and in the absence of growth factors, both parasitic antigens stimulated phosphorylation of mTOR (Ser2448) in BMDCs, being this effect higher with pLL compared to HF ( Figure 5). Previous studies in E. granulosus have shown in GM-CSF derived DCs or M-CSF derived macrophages that exposure to pLL strongly inhibited PI3K, Akt and GSK3 phosphorylation induced by LPS, and that stimulation of DCs with pLL alone inhibited basal phosphorylation of these proteins 37,38 . On the other hand, Eg excretory/secretory products induced alternative activated macrophages phenotype (M2), through the activation of the PI3K/AKT/mTOR pathway 36 .…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations